Analysis The Malino Beautiful Festival On Management Strategy Of Tourist Visits In Gowa Regency - I Nyoman Siryayasa; Masri Ridwan; Aris Baharuddin (PINISI Discretion Review, 2022)
This research is to answer the management strategy for visits tourists as well as f -factors which required for increasing the implementation of the Beautiful Malino Festival as a Tourist Attraction a. Surveys and documentation were carried out before and during the Beautiful Malino festival which took place in September in Malino, Tinggimincong District, Gowa Regency, South Sulawesi. The research approach uses descriptive qualitative , data collection through the distribution of questionnaires, interviews and literature study. The implementation of the Beautiful Malino Festival was able to attract an increase in the number of tourist visits to Malino since 2017 the number of tourists reached 20,000 people, in 2018 it reached 20,000 people. 50,000 people and in 2019 up 300% or reaching 80,000 people . The results of the study revealed that the strategy adopted in increasing tourist visits was due to the development of tourist destinations through offering affordable tour packages , collaboration with relevant agencies through funding and sponsorship assistance and promotions carried out regularly by the Gowa district government through social media, attracting influencers, banners, billboards, and print media. This study recommends improving the accessibility of tourist movements in Malino destinations and providing accommodation facilities that can accommodate large numbers of tourists.